Viscous effects on liquid sloshing under external excitations. (1st January 2019) - Jin, Xin; Lin, Pengzhi
Abstract: The viscous effects on liquid sloshing under external excitations were investigated in this study. A 3D two-phase flow numerical model was adopted to simulate sloshing of highly viscous fluids by properly resolving boundary layer near tank walls. The numerical model was validated against available analytical solutions and previous numerical results. In addition, the laboratory experiment of the sloshing of glycerin was conducted in this study, providing additional data for numerical model verification. The effects of liquid adherence to side walls due to high viscosity was discussed. The verified numerical model was then employed to study the sloshing of fluids with different kinematic viscosities ranging from 10 −6  m 2 /s to 10 −2  m 2 /s. The free surface profiles during the sloshing wave impact on the wall were analyzed, in connection with the pressure response characteristics. Special attentions were made on the extended rising time during the impact process for fluids with large viscosity. The fast Fourier transform technique was used to study the frequency responses of the sloshing. The critical value of viscosity, at which the response type shifts from natural frequency response to external excitation response, was identified. Finally, the comparisons between water and glycerin under six degree-of-freedom excitations were presented and discussed. Highlights: The adequate resolution of the boundary layer is important for high viscous fluids in numerical simulation. For resonant excitations, the bimodal fetures of pressure responses are gradually weakened as the increase of viscosity. The viscosity enhances both rising time and phase shift between the first peak pressure and peak excitation acceleration. There exists a critical viscosity, where response frequency shifts from natural and forcing frequency to forcing frequency.